An Overview of Fiber‐Shaped Batteries with a Focus on Multifunctionality, Scalability, and Technical Difficulties. Issue 5 (30th July 2019) - Mo, Funian; Liang, Guojin; Huang, Zhaodong; Li, Hongfei; Wang, Donghong; Zhi, Chunyi
Abstract: Flexible and wearable energy storage devices are receiving increasing attention with the ever‐growing market of wearable electronics. Fiber‐shaped batteries display a unique 1D architecture with the merits of superior flexibility, miniaturization potential, adaptability to deformation, and compatibility with the traditional textile industry, which are especially advantageous for wearable applications. In the recent research frontier in the field of fiber‐shaped batteries, in addition to higher performance, advances in multifunctional, scalable, and integrable systems are also the main themes. However, many difficulties exist, including difficult encapsulation and installation of separators, high internal resistance, and poor durability. Herein, the design principles (e.g., electrode preparation and battery assembly) and device performance (e.g., electrochemical and mechanical properties) of fiber‐shaped batteries, including lithium‐based batteries, zinc‐based batteries, and some other representative systems, are summarized, with a focus on multifunctional devices with environmental adaptability, stimuli‐responsive properties, and scalability up to energy textiles, with the hope of enlightening future research directions. Finally, technical challenges in the realistic wearable application of these batteries are also discussed with the aim of providing possible solutions and new insights for further improvement. Abstract : Fiber‐shaped batteries display a unique one‐dimensional configuration with merits of superior flexibility, miniaturization potential, and adaptability to deformation. The recent advances in fiber‐shaped lithium‐based batteries, zinc‐based batteries, and other promising systems are introduced. Furthermore, multifunctional, scalable, and integrable systems are highlighted with the hope of enlightening future research directions. Challenges and perspectives for realistic wearable applications are also discussed.